Polska bibliografia Tertuliana za lata 1998-2023 - Wysocki, Marcin (Vox Patrum, 2024)
Bibliography of the Polish scientific works on Tertullian published in years 1998-2023. It is a continuation of the bibligraphy: K. Obrycki, Polska bibliografia Tertuliana za lata 1982-1997, CT 68/2 (1998) p. 109-112.